(untitled) (Journal of human and social sciences, 2023)
This study aims to propose a model to improve the Libyan economic situation by achieving the main macroeconomic objectives: increasing GDP growth, reducing unemployment and inflation, and attaining balance in the balance of payments. The study argues that the optimal way to achieve these goals is through ensuring the availability of foreign currencies and maintaining exchange rate stability. Stable exchange rates directly enhance the balance of payments and reduce inflation, given Libya’s high degree of economic openness. Exchange rate stability also contributes to GDP growth and lower unemployment. The study emphasizes the need to reduce excessive dependence on crude oil exports and to develop alternative sources of national income through the proposed model.